Evapotranspiration An Overview - Alexandris, Stavros G. (IntechOpen, 2013)
Evapotranspiration - An Overview contains recent advances in the physics of evaporation and transpiration from a typical experimental site to large scale areas. It incorporates many years of authors experience with the latest research on the methods and the models used worldwide, engaging advanced technology and modern instrumentation. The reader benefits from the in-depth analysis and the diverse sites and settings, where the models, applications and methods are tested. Weather conditions, soil moisture, geology, climatic systems are examined for their role and influence on the theoretical and actual water demand by the atmosphere in the earth's ecosystem. This book not only provides students and scientists with the information to improve the procedures for estimating evapotranspiration, but will also help them to manage and evaluate the observed data.